2022
DOI: 10.3389/fimmu.2021.801410
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Granulocytic Myeloid-Derived Suppressor Cells May Be a Good Marker of Survival in the Follow-Up of Patients With Severe COVID-19

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a disease (coronavirus disease 2019, COVID-19) that may develop into a systemic disease with immunosuppression and death in its severe form. Myeloid-derived suppressive cells (MDSCs) are inhibitory cells that contribute to immunosuppression in patients with cancer and infection. Increased levels of MDSCs have been found in COVID-19 patients, although their role in the pathogenesis of severe COVID-19 has not been clarified. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…Furthermore, blood M-MDSCs showed a negative correlation with activated T cells ( 12 ). In a recent study, we also found that peripheral blood G-MDSCs could serve as a marker for mortality in ICU-admitted patients with COVID-19 ( 13 ). Other studies have also suggested that MDSCs might influence both disease severity and mortality ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, blood M-MDSCs showed a negative correlation with activated T cells ( 12 ). In a recent study, we also found that peripheral blood G-MDSCs could serve as a marker for mortality in ICU-admitted patients with COVID-19 ( 13 ). Other studies have also suggested that MDSCs might influence both disease severity and mortality ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 76%
“…Significantly, a link between MDSCs and COVID-19 has been identified in a number of recent investigations ( Table 1 ). Compared with healthy subjects or patients with mild COVID-19, the frequency of PMN-MDSCs in the peripheral blood of COVID-19 increases with disease exacerbation, especially in severe instances and deceased patients, and proliferating PMN-MDSCs will further suppress T cells, resulting in a reduction in lymphocytes and further compromising the host immune response, so establishing a vicious cycle ( 7 , 20 , 44 , 45 ). Comparison with indicators reflecting disease severity (levels of C-reactive protein, ferritin, and lactate dehydrogenase) demonstrated that these indicators were elevated with PMN-MDSCs in severe cases, especially immature PMN-MDSCs, confirming a positive correlation between PMN-MDSCs and COVID-19 severity ( 41 ).…”
Section: Mdscs As a Target For Infectious Lung Diseasesmentioning
confidence: 99%
“…In contrast to these results, Japanese researchers found that the frequency of PMN-MDSCs (but not other MDSC subgroups) may be transiently elevated in patients surviving severe COVID-19 compared to patients dying from severe COVID-19, and the investigators suggest that PMN-MDSCs may reduce detrimental immune responses and be associated with genetic factors ( 36 ). In severely sick individuals, low levels of PMN-MDSCs may aid in survival ( 45 ). However, the majority of investigations have revealed that the frequency of M-MDSCs in peripheral blood following COVID-19 therapy is substantially linked with disease severity ( 8 , 37 ).…”
Section: Mdscs As a Target For Infectious Lung Diseasesmentioning
confidence: 99%
“…The results of the follow-up demonstrated steadily elevated counts of MDSCs until death in the peripheral blood of patients who eventually died. Discharged patients experienced a transitory increase in the counts of MDSCs during the first two weeks after ICU admission with a subsequent decline to baseline levels at discharge [ 103 ]. Similarly, Trombetta et a .…”
Section: The Role Of Mdscs In Covid-19mentioning
confidence: 99%